Analisis Distribusi Obat Rawat Inap di Instalasi Farmasi RSUD Tarakan Jakarta Pusat - Ika Purwidyaningrum (Jurnal Farmasi Indonesia, 2011)
Drug management in hospital which consist of stages are selection, procurement, distribution and use. Result of preliminary observation done in Pharmacy Installation of Tarakan Hospital found some inefficiency problem in distribution steps such as expired and damage control, conformity of record to physical checks on drug management, etc. Therefore, it necessary to evaluation the efficiency rate of inpatient ward drug management distribution. Research using a design description is retrospective and concurrent with the evaluation of documents relating to inpatient drug distribution process. The study used a sample of drugs including medicines criteria Class A. Data collected in the form of qualitative and quantitative data from observations of documents and interviews with relevant officers. Presentation of data in tabular and textual descriptions, evaluations descriptively using SPSS. Measurement of the efficiency of drug distribution is done by using indicators of the efficiency of Depkes, Pudjaningsih (1996) and WHO (1993), then compared with the standard or the results of a study to determine the existence of inefficiency. The results showed, according to several indicators of drug distribution and hospitalization have not beenefficient. Inefficiency drug management indicators at this stage of the distribution occurs on a match between the physical card stock is 93,27%; the damaged and expired drugs in 2008 was 0,23% in 2009 was 0,48%; TOR in 2008 was 6 times and in 2008 was 6,9 times.